Two possible source regions for central Greenland last glacial dust - Újvári, Gábor; Stevens, Thomas; Svensson, Anders; Klötzli, Urs S.; Manning, Christina; Németh, Tibor; Kovács, János; Sweeney, Mark R.; Gocke, Martina; Wiesenberg, Guido L. B.; Markovic, Slobodan B.; Zech, Michael (Geophysical research letters, 2015)
Dust in Greenland ice cores is used to reconstruct the activity of dust‐emitting regions and atmospheric circulation. However, the source of dust material to Greenland over the last glacial period is the subject of considerable uncertainty. Here we use new clay mineral and <10 µm Sr–Nd isotopic data from a range of Northern Hemisphere loess deposits in possible source regions alongside existing isotopic data to show that these methods cannot discriminate between two competing hypothetical origins for Greenland dust: an East Asian and/or central European source. In contrast, Hf isotopes (<10 µm fraction) of loess samples show considerable differences between the potential source regions. We attribute this to a first‐order clay mineralogy dependence of Hf isotopic signatures in the finest silt/clay fractions, due to absence of zircons. As zircons would also be absent in Greenland dust, this provides a new way to discriminate between hypotheses for Greenland dust sources. Key Points New clay mineral and Sr‐Nd‐Hf data for the last glacial Greenland dust sources Clay and Sr‐Nd data suggest two equally plausible Greenland dust sources Hf isotopes of fine grain loess separates may be source diagnostic